A simplified model of catenary action in reinforced concrete frames under axially restrained conditions - Pham, Anh Tuan (2018)
From previous experimental studies on missing column scenarios, catenary action could provide beneficial effects on structures during load redistribution after a target column is suddenly removed under an alternative load path procedure to assess structural resistance to progressive collapse. However, full-scale structural tests are costly and time consuming. Equally, finite-element models require in-depth expertise and large computing resources. Practising engineers are not amenable to this approach for preliminary sizing of members or for a quick assessment of structural resilience. To address this need, this paper provides a simplified semi-analytical model for predicting structural response under a column loss scenario. The model is constructed based on finite-element simulations and is verified by test results. The simplified model idealises the structural response of reinforced concrete beam–column sub-assemblages under column loss scenarios as a piecewise multi-linear curve. It shows good agreement with published test results and validated finite-element simulations.